Wednesday
March 29, 2017

Post a New Question

Posted by on .

Express (5x+2)/(2x-1)(x+1) into partial fractions and hence expand the expression as a series in ascending power of x giving the first 4 terms

  • math - ,

    (5x+2)/(2x-1)(x+1)
    = 3/(2x-1) + 1/(x+1)

    Now, think of geometric series where the infinite sum is
    S = a/(1-r)

    3/(2x-1) = -3/(1-2x) = -3(1+(2x)+(2x)^2 + (2x)^3)
    = -3(1+2x+4x^2+8x^3)
    = -3 - 6x - 12x^2 - 24x^3

    Similarly for 1/(x+1) so we end up with


    -2 - 7x - 11x^2 - 25x^3 - ...

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question